Invention : recycling - Discovery Channel (USA: Discovery Channel School, 2003)
Delves into the young, but essential, recycling movement. Features a biodegradable golf tee made of sawdust and applesauce, and a fleece jacket made from recycled plastic bottles.
Executive producer, Adrienne Schure
Keywords: Inventions; Recycling; Technology